The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s10265-022-01429-1
|View full text |Cite
|
Sign up to set email alerts
|

Does selection occur at the intermediate zone of two insufficiently isolated populations? A whole-genome analysis along an altitudinal gradient

Abstract: Adaptive divergence would occur even between the insu ciently isolated populations when there is a great difference in the environments between their habitats. The individuals present in the intermediate zone of the two divergent populations are expected to have an admixed genetic structure due to gene ow. A selective pressure that acts on the genetically admixed individuals may limit the gene ow and promote the adaptive divergence. Here, we addressed a question whether the selection occurs in the genetically … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…While there have been a few studies on population structure in Japanese A. halleri , they relied on a limited number of loci and sampling locations (Sato and Kudoh, 2014) or focused on a microgeographic scale (Kubota et al, 2015; Yoshida et al, 2023). In this study, by using full-genome re-sequencing data from region-wide samples, we revealed a population structure that showed a clear geographic pattern (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While there have been a few studies on population structure in Japanese A. halleri , they relied on a limited number of loci and sampling locations (Sato and Kudoh, 2014) or focused on a microgeographic scale (Kubota et al, 2015; Yoshida et al, 2023). In this study, by using full-genome re-sequencing data from region-wide samples, we revealed a population structure that showed a clear geographic pattern (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This study focused on Arabidopsis halleri, a perennial herb distributed in East Asia and Europe. This species has been used extensively for evolutionary and ecological studies (reviewed in Honjo and Kudoh, 2019; Koch, 2018), such as self-incompatibility (Castric and Vekemans, 2004; Durand et al, 2020), heavy metal hyperaccumulation (Krämer, 2010; Stein et al, 2017), and adaptation to high altitudes (Kubota et al, 2015; Yoshida et al, 2023; Yumoto et al, 2021). Five subspecies are recognized in A. halleri : A. halleri subsp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations